Awareness about sanitary toilets in a rural area of north Karnataka, India: a cross sectional study - Jeratagi, Sidharaj; Kumar, Yogesh; Mallapur, Maheshwar D. (International Journal Of Community Medicine And Public Health, 2017)
Background: As improvement in sanitation is one of the goal among Millennium Development Goals, awareness and lack of sanitary toilet in rural areas is still a major public problem. The objectives were to study the awareness level about sanitary toilet in a rural area. Methods: Study participants included 400 adults from Sonatti village of Belgaum district of north Karnataka. Pre-tested questionnaire was used to collect necessary information including socio demographic variables by house to house survey. Ethical clearance was obtained from IEC on human subjects of Jawaharlal Nehru Medical College, Belgaum. Informed consent was taken before collecting data from all the participants. Results: In this study most of study participants 173 (43.3%) were aged between 18 to 30 years. Majority of 164 (41.0%) were farmers and most of them 197 (49.2%) belonged to Class IV socioeconomic strata. Only 3(0.7%) had a household latrine. About 80% of participants showed average knowledge, 50% of participants showed good attitude and 62% of participants showed average practice. Awareness of sanitary toilet use was significantly associated with higher socioeconomic status and higher education. Conclusions: The present study revealed that awareness about sanitary latrine was very poor. Practice of open air defecation was very high. The overall assessment of participants revealed that there is a need to create more awareness regarding sanitary toilet use in rural areas.